2014
DOI: 10.1111/jfb.12515
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐sea bigscales, pricklefishes, gibberfishes and whalefishes (Teleostei: Stephanoberycoidei) off Brazil: new records, range extensions for the south‐western Atlantic Ocean and remarks on the taxonomy of Poromitra

Abstract: The Stephanoberycoidei includes 23 genera and c. 94 species of deep-sea teleosts commonly known as bigscales, pricklefishes, gibberfishes and whalefishes. Stephanoberycoidei is one of the least known groups of deep-sea fishes, in spite of their apparent relative abundance in meso and bathypelagic depths. Nine species of the Stephanoberycoidei are reported here for the first time in Brazilian waters, and most of them represent new range extensions for the south-western Atlantic Ocean. Those species are Melampha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 50 publications
(159 reference statements)
1
23
0
Order By: Relevance
“…For instance, for decades the crested bigscale Poromitra crassiceps (Günther 1878) has been the only stephanoberyciform reported in Brazilian waters (Menezes et al ., ). A recent study, however, revealed that the diversity of this group in the area is much higher, with 13 species reported so far (Mincarone et al ., ). Even some circumglobal pelagic sharks were only recently reported off Brazil, such as the goblin shark Mitsukurina owstoni Jordan 1898 (Holanda & Asano Filho, ), the kitefin shark Dalatias licha (Bonnaterre 1788) (Soto & Mincarone, ) and the megamouth shark Megachasma pelagios Taylor, Compagno & Struhsaker 1983 (Amorim et al ., ).…”
Section: Habitatsmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, for decades the crested bigscale Poromitra crassiceps (Günther 1878) has been the only stephanoberyciform reported in Brazilian waters (Menezes et al ., ). A recent study, however, revealed that the diversity of this group in the area is much higher, with 13 species reported so far (Mincarone et al ., ). Even some circumglobal pelagic sharks were only recently reported off Brazil, such as the goblin shark Mitsukurina owstoni Jordan 1898 (Holanda & Asano Filho, ), the kitefin shark Dalatias licha (Bonnaterre 1788) (Soto & Mincarone, ) and the megamouth shark Megachasma pelagios Taylor, Compagno & Struhsaker 1983 (Amorim et al ., ).…”
Section: Habitatsmentioning
confidence: 97%
“…Fishing surveys focused on the evaluation of biological parameters of fish stocks along the south‐western Atlantic shelf and slope have led to significant improvements in the knowledge of the diversity and biology of deep‐sea fishes. As result of these and similar initiatives, an impressive number of new distribution records has been provided and several new species were discovered in the past decade, covering a wide range of taxonomic groups, including Myxinidae (Mincarone, ; ), Scyliorhinidae (Soares et al ., ), Rajidae (Carvalho et al ., ), Anguilliformes (Melo, ; Melo et al ., ); Sternoptychidae (Lima et al ., ), Chiasmodontidae (Melo, ), Ophidiiformes (Franco et al ., ; Mincarone et al ., ; Nielsen, ; Nielsen et al ., ; Nielsen et al ., ), Stephanoberyciformes (Mincarone et al ., ), Gadiformes (Melo et al ., ), Ipnopidae (Franco et al ., ), Zoarcidae (Anderson & Mincarone, ; Mincarone & Anderson, ) and Bramidae (Carvalho‐Filho et al ., ).…”
Section: Habitatsmentioning
confidence: 99%
“…There is also an increase in the knowledge on the diversity of several Brazilian deep-sea fish groups in addition to the Ophidiiformes (e.g., Carvalho et al, 2005;Anderson & Mincarone, 2006;Mincarone & Anderson, 2008;Franco et al, 2009;Melo et al, 2009Melo et al, , 2010Lima et al, 2011;Mincarone et al, 2014 ). That situation results largely from the fact that only in the last decade collections made in recent fishing surveys performed offshore Brazil started to be properly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Unless stated otherwise, gill raker number refers to the total number of rakers in the first gill arch. Species identifications were based on descriptions and taxonomic keys provided by Goode and Bean (1895), Parr (1934Parr ( , 1946, Harry (1952), Rofen (1959), Bigelow (1961), Ebeling (1962), Abe and Hotta (1963), Richardson and Garrick (1964), Abe et al (1965), Maul (1969), Ebeling and Weed (1973), Fedorov et al (1987), Paxton (1989), McEachran and Fechhelm (1998), , Paxton and Trnski (2003), Kotlyar (2004bKotlyar ( , 2004cKotlyar ( , 2005Kotlyar ( , 2008aKotlyar ( , 2008bKotlyar ( , 2009aKotlyar ( , 2009bKotlyar ( , 2009cKotlyar ( , 2010Kotlyar ( , 2011aKotlyar ( , 2011bKotlyar ( , 2012aKotlyar ( , 2012bKotlyar ( , 2013Kotlyar ( , 2014Kotlyar ( , 2015aKotlyar ( , 2015bKotlyar ( , 2015cKotlyar ( , 2016aKotlyar ( , 2016bKotlyar ( , 2016cKotlyar ( , 2019Kotlyar ( , 2020, Iwasaki (2009), and Mincarone et al (2014). Institutional abbreviations follow Sabaj (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Species of the group are reported from all oceans except the Arctic and the Mediterranean Sea (Ebeling, 1962;Kotlyar, 2004bKotlyar, , 2004cKotlyar, , 2005Kotlyar, , 2008aKotlyar, , 2008bKotlyar, , 2009bKotlyar, , 2009cKotlyar, , 2010Kotlyar, , 2011aKotlyar, , 2011bKotlyar, , 2012aKotlyar, , 2012bKotlyar, , 2013Kotlyar, , 2019Sutton et al, 2020). Juveniles occur in shallow oceanic waters, whereas adults occur below 100-200 m to depths greater than 3,000 m (Ebeling, 1962;Keene, 1987;Kotlyar, 2004a;Mincarone et al, 2014). In the Brazilian EEZ, ten species of the Melamphaidae were previously recorded: Melamphaes hubbsi, M. polylepis, M. typhlops, Poromitra crassiceps, P. megalops, Poromitra sp., Scopeloberyx opisthopterus, Scopeloberyx robustus, Scopelogadus beanii, and Scopelogadus mizolepis (Günther, 1887;Keene, 1987;Campos et al, 2008;Costa and Mincarone, 2010;Mincarone et al, 2014;Judkins and Haedrich, 2018).…”
Section: Melamphaidaementioning
confidence: 99%